Analisis Electronic Word of Mouth dalam Pembelian Produk di Social Commerce TikTok Shop - Melinda Rosilawati; Annisa Septi Amaliyah; Eli Masnawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
TikTok Shop is one of the most popular social commerce for Indonesian people to make product purchase transactions. Advertising on TikTok Shop social commerce is inseparable from Electronic Word of Mouth (e-WOM). In today's era, e-WOM is considered as one of the important aspects that influences online shopping activities. This study aims to determine the effect of e-WOM on consumers in purchasing products on TikTok Shop social commerce. The type of research used is qualitative with a descriptive method in order to obtain an explanation of the phenomenon of e-WOM. The data collection technique was carried out by interviewing respondents who were the samples in this study. The sample in this study used a purposive sampling technique. There are three indicators that are used to assess e-WOM, namely intensity, consumer opinion, and content. The results of these three indicators show that e-WOM has been implemented well as a consideration for consumers in deciding to purchase products on TikTok Shop. This is expected to be a reference for sellers on TikTok Shop to always create marketing strategies by utilizing e-WOM.